Analisis Stabilitas Struktur Rangka Gudang terhadap Beban Hoist Crane 2 Ton Menggunakan Metode Finite Element - Adi, Abshar; Teguh Santoso, Deri (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
This study aims to conduct a comparative study of the loading capacity and stability of the main frame of the existing warehouse at PT. XYZ to accommodate the installation of a 2-ton hoist crane frame. The analysis is carried out by considering the static load generated by the hoist crane, including the self-weight of the crane frame, maximum lifting load, and shock factor. The methods used include collecting data on dimensions and materials of the existing warehouse frame, calculating the working loads, and modeling and structural analysis using finite element software. Several hoist crane frame installation configurations will be analyzed to identify the safest and most efficient option by considering the loading capacity limitations and stability requirements of the main frame of the warehouse. The results of this study are expected to provide clear recommendations regarding the feasibility of installing a 2-ton hoist crane on the existing warehouse frame, as well as identifying potential reinforcements that may be needed to ensure operational safety and structural integrity of the building. This comparative study will evaluate various aspects such as stress, deflection, and safety factors on the structural elements of the warehouse frame for each crane installation configuration, thus providing a strong basis for decision making at PT. XYZ. the structural elements of the warehouse frame for each crane installation configuration, thus providing a strong basis for decision making at PT. XYZ.